PERBANDINGAN AKTIVITAS ENZIM ASPARTAT AMINOTRANSFERASE ANTARA SERUM YANG HEMOLISIS DAN SERUM NORMAL DENGAN METODE KINETIK-IFCC - Istik Nuril Qomari; Muhammad Sungging Pradana; Dheasy Herawati (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2022)
Aspartic aminotransferase (AST) is a mitochondrial enzyme that catalyzes the back and forth transfer of amino groups from aspartic acid to ?-oxaloacetic acid to form glutamic acid and oxaloacetic acid. AST is contained in erythrocytes so that if there is hemolysis, a ruptured erythrocyte will cause an increase in the activity of the AST enzyme that comes out of the erythrocyte. This study aims to determine the effect of hemolysis in serum on AST enzyme activity. This research method is experimental by comparing normal serum with hemolytic serum. The research sample involved 30 employees of the Manding Sumenep Public Health Center who would be examined for the AST enzyme activity. The results showed that the AST enzyme activity in normal serum had an average of 24.367 IU / L, while the average hemolytic serum was 39.3 IU / L. Based on the results of these data, it shows that there is an increase in AST enzyme activity in hemolytic serum compared to normal serum.